2003
DOI: 10.1179/135100003225002952
|View full text |Cite
|
Sign up to set email alerts
|

The Haldane malaria hypothesis: facts, artifacts, and a prophecy

Abstract: Heterozygous thalassemia and sickle cell disease produce mild hematological symptoms but provide protection against malaria mortality and severe malaria symptoms. Two explanations for resistance are considered in the literature - impaired growth of the parasite or enhanced removal by the host immune cells. A critical overview of studies that connect malaria resistance with impaired intra-erythrocytic growth is presented. All studies are fraught with two kinds of bias. The first one resides in the impossibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 33 publications
(49 reference statements)
0
9
0
Order By: Relevance
“…Firstly, it has been shown that intra-erythrocytic parasite growth is greatly inhibited by HbS polymerization when oxygen levels drop below 5%. Secondly, higher parasite-infected sickle erythrocyte phagocytosis by host immune cells has been observed when compared to infected normal erythrocytes (Smith et al, 2002;Akide-Ndunge et al, 2003;Roberts and Williams, 2003;Ayi et al, 2004;Cabrera et al, 2005).…”
Section: Sickle-cell Traitmentioning
confidence: 97%
See 1 more Smart Citation
“…Firstly, it has been shown that intra-erythrocytic parasite growth is greatly inhibited by HbS polymerization when oxygen levels drop below 5%. Secondly, higher parasite-infected sickle erythrocyte phagocytosis by host immune cells has been observed when compared to infected normal erythrocytes (Smith et al, 2002;Akide-Ndunge et al, 2003;Roberts and Williams, 2003;Ayi et al, 2004;Cabrera et al, 2005).…”
Section: Sickle-cell Traitmentioning
confidence: 97%
“…According to Haldane's malaria hypothesis (Haldane, 1949;Yuthavong and Wilairat, 1993;Smith et al, 2002;Duffy and Fried, 2006;Pasvol, 2006), this could result in a "balanced polymorphism" where the homozygote's hematological disadvantage is balanced by the resistance to malaria displayed by the heterozygote (Yuthavong and Wilairat, 1993;Agarwal et al, 2000;Smith et al, 2002;Akide-Ndunge et al, 2003).…”
Section: Introductionmentioning
confidence: 96%
“…Two general protective mechanisms had been considered in the literature: restricted parasite growth and enhanced immune retrieval of the parasitized RBCs. Much of the early work is conflictive and confusing, mainly because of the limitations of in vitro studies to reproduce the conditions in vivo (1). Recent work (9,59,135) strongly suggests that resistance in AS RBCs is caused by enhanced phagocytosis of RBCs infected with ring stage parasites in response to alterations of the membrane surface associated with increased hemichrome formation, aggregated band 3, elevated autologous IgG, and complement C3c fragments.…”
Section: A Sickle Cell Anemia: First "Molecular Disease"mentioning
confidence: 97%
“…43,44 These abnormalities may affect the structure of hemoglobin, 45,46 the RBC membrane, 47,48 or RBC metabolism, [49][50][51] generating a large diversity of pathologies affecting millions of people worldwide. The most widely distributed of these pathologies are sickle cell anemia, thalassemias, 52-54 ovalocytosis, 48,55 hereditary spherocytosis, 56 and glucose-6-phosphate dehydrogenase (G6PD) deficiency.…”
Section: Discussionmentioning
confidence: 99%